2006
DOI: 10.1159/000095238
|View full text |Cite
|
Sign up to set email alerts
|

Non-telomeric sites as evidence of chromosomal rearrangement and repetitive (TTAGGG)<sub>n </sub>arrays in heterochromatic and euchromatic regions in four species of <i>Akodon</i> (Rodentia, Muridae)

Abstract: Comparative studies among four species – Akodonazarae (2n = 38), A. lindberghi (2n = 42), A. paranaensis (2n = 44) and A. serrensis (2n = 46) – employing classic cytogenetics (C- and G-bands) and fluorescence in situ hybridization with telomeric (TTAGGG)n sequencesare reported here. Non-telomeric signals in addition to the regular telomeric sites were detected in three species:A. azarae, A. lindberghi and A. serrensis. One interstitial telomeric site (ITS) was observed proximally at the long arm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
31
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 64 publications
7
31
0
2
Order By: Relevance
“…However, disclosing of large blocks of telomeric sequences within C-negative pericentromeric regions of acrocentric chromosomes is evidence for the occurrence of co-localization of the telomeric sequences with euchromatin material. A similar phenomenon has been described for chromosomes of Brazilian rodents of the genus Akodon and was explained by the presence of TTAGGG-like sequences in such euchromatin regions (Ventura et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…However, disclosing of large blocks of telomeric sequences within C-negative pericentromeric regions of acrocentric chromosomes is evidence for the occurrence of co-localization of the telomeric sequences with euchromatin material. A similar phenomenon has been described for chromosomes of Brazilian rodents of the genus Akodon and was explained by the presence of TTAGGG-like sequences in such euchromatin regions (Ventura et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…These non-telomeric sites of (TTAGGG)n repeats and the colocalization of telomeric repeats and satellite DNA sequences are most likely the result of chromosome rearrangements involving the chromosome ends (including inversions, centric fusion, and telomere-to-telomere fusion) (Go et al, 2000;Li et al, 2000;Lear, 2001;Hartmann and Scherthan, 2004;Ventura et al, 2006;Tsipouri et al, 2008). In addition, sequence analysis of ITSs revealed that the interstitial arrays of (TTAGGG)n repeats could be inserted at intrachromosomal sites through double-strand breaks in ancient chromosomes (Azzalin et al, 2001;Nergadze et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning sigmodontine rodents, no ITS reflect the remarkable rearrangements that relate Akodon cursor and A. montensis (Fagundes et al 1997b), or this species and the more distant Bolomys lasiurus (Fagundes and Yonenaga-Yassuda 1998), nor show ITS the chromosomes that result from tandem fusions in Nectomys (Silva and Yonenaga-Yassuda 1998). On the other hand, the homeologous telocentric first pairs of A. azarae and A. boliviensis, which present a noticeable proximal IT (Viera et al 2004, Ventura et al 2006, correspond to pairs 1 plus 20 of A. paranaensis and A. serrensis (Ventura et al 2006).…”
mentioning
confidence: 97%